Fatigue Strength Analysis of Planet Carrier in MW Level Wind Turbine Gearbox - Shi Pengfei; Chu Jingchun; Yuan Ling; Sun Li; Fan Xiaoliang; Pan Lei; Li Yingchang (Jixie chuandong)
Based on the finite element analysis model of the low speed stage of the MW wind turbine gearbox,the fatigue damage of the low speed gearbox is studied. Based on the analysis of the ANSYS-workbench and the ANSYS classic,the stress condition of the low speed level planet carrier of the wind turbine is obtained.The S-N curve of planet carrier is got based on the design specification of GL2010. The fatigue load spectrum of the planet carrier is calculated by the rain flow cycle counting method. Finally,based on the combination of presents a rain flow counting method with Palmagren-Miner damage theory and safety factor to calculate the fatigue damage method by using the n Code/design life software,the fatigue damage and minimum safety factor of the low speed level planet carrier of the wind power gearbox is obtained. The analysis results show that the proposed method is reliable and practical,a more accurate analysis method for the fatigue analysis on planet carrier in MW level wind turbine gearbox is provided and it also has a certain practical significance.